Knowledge, Attitude and Awareness among Diabetic vs. Non-Diabetic Patients about the Association between Diabetes and Oral Health - Jaswinder Kaur; Gurleen Kaur Pruthi; Harsimran Singh Kapoor; Vishwas Narang; Akaljot Kaur; Aakash Gupta (Indian Journal of Dental Research)
Background: Global prevalence of diabetes is rapidly increasing with an estimate to affect 593 million worldwide by 2035. Current evidence clearly states an association between oral diseases and diabetes mellitus with manifestations like periodontitis, peri-implantitis, xerostomia, etc. Despite this obvious link, knowledge, awareness and attitude of general population towards this are not fully understood. Aims: To assess public knowledge and awareness on association between diabetes and oral health and assess their attitude towards oral hygiene care and maintenance. Methods and Materials: A three-part structured questionnaire was developed with multiple choice questions and circulated among patients visiting a private dental college. A total of 502 questionnaires were evaluated, and results were statistically analysed. Statistical Analysis Used: Student-t test and Chi-square test using SPSS software. Results: Majority of the participants were male and lived in urban area. 41.8% respondents had diabetes, out of which 86.7% had no awareness of the type. A significant number of non-diabetic individuals had awareness of excessive sugar intake as a cause of diabetes. Greater number of diabetic patients (96.7%) reported dry mouth, whereas only 53.3% had periodontal complications. 90% participants use tooth brush as oral hygiene aid. Only 10.6% participants follow regular dental visits. Majority of subjects (60.6%) listed their friends and family as major source of information. Conclusion: More people are aware of systemic complications of diabetes as compared to oral problems. A better interdisciplinary relationship is required among dentists and physicians to improve knowledge and awareness of general population.